The determinants of capital structure and internal factors that influence the performance of commercial banks in Botswana - Mapororo, Beauty (Department of Finance and Tax, 2019)
The main objectives of the study are to empirically explore the determinants of capital structure for commercial banks in Botswana and to determine the internal factors that influence the performance of the banks. A study on what determines capital structure for banks and the factors that influence performance has never been done for Botswana, thus the study aims to add on to the existing literature. Quantitative approach, mainly multiple regression models and descriptive statistics, are used to find the relationship among the independent and dependent variables based on the five years data for the period 2012 to 2016. The dependent variables are the total leverage, short-term, and long-term leverage and the performance measure is the Return on Assets. The empirical results conclude that in accordance with the pecking order theory and the finance literature, debt has an overall negative relationship with banks performance, and the bigger the bank the less debt is employed. Further, this study proves efficiency theory for Botswana banks. That is the relationship between capital adequacy and liquidity with return on assets did not provide statistically-significant results. It is hoped that the results of the study will assist managers on employing the right balance of debt and equity to achieve desired performance.